Peningkatan Literasi Keuangan Digital Ibu Rumah Tangga tentang Perdagangan Berjangka Komoditi Legal - Rahmawati, Siti Rusdiana; Zawawi, Zawawi (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service aims to enhance digital financial literacy for 25 housewives in Desa Sawotratap with a literacy index of 65.58% ((BPS) 2025), vulnerable to illegal investment scams due to limited understanding of legal Commodity Futures Trading Interactive counseling methods using slide presentations, group discussions, and QA introduced PT Trijaya Pratama Futures (TPFx) supervised by BAPPEBTI, along with products such as gold, forex, Nasdaq 100, and SP 500 with a capital of Rp100,000. Results show that 87% (22/25 participants) can distinguish between legal and illegal instruments, surpassing the 4.05-point increase reported by (Hartarto et al. 2022). The discussion approach effectively transforms negative perceptions of Commodity Futures Trading into an understanding of family risk management, contributing to the prevention of digital fraud and improving welfare in Desa Sawotratap.